The Effect of Musharakah and Murabaha Financing on Profitability with Non-Performing Financing as a Moderating Variable (in Sharia Business Units Registered with the Financial Services Authority) - Awin Rahma Zulvia; Oyong Lisa; Djuni Farhan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to analyze the effect of Musharakah and murabahah financing on profitability in Islamic business units, as well as to examine the impact of Non-Performing Financing (NPF) on profitability. Additionally, this research assesses whether NPF can moderate the effect of Musharakah and murabahah financing on profitability. Thus, the study is expected to provide comprehensive insights into the relationship between types of Islamic financing, financing quality, and financial performance of Islamic business units. The research method used is a quantitative approach with eight Islamic business units selected using purposive sampling between 2020 and 2023. The data were analyzed using Moderated Regression Analysis to test the hypotheses proposed in the study. The results indicate that Musharakah financing has a negative and significant effect on profitability, with a coefficient of -3.562 and a probability value of 0.001. This suggests that higher Musharakah financing is associated with decreased financial performance of Islamic banks. Conversely, murabahah financing has a positive and significant effect on profitability, with a coefficient of 4.593 and a probability value of 0.000, meaning that higher murabahah financing is associated with improved financial performance. NPF is not able to moderate the effect of Musharakah on profitability, with a coefficient of -2.667 and a probability value of 0.013, but it is able to moderate the effect of murabahah on profitability, with a coefficient of 8.981 and a probability value of 0.000. These results are consistent with several previous studies that support these findings.